Apple Logic Pro 8 essentials training - Copeland, Patrick; Safari eBooks ([United States?] : HowAudio.com, 2009)
"With this latest release, Apple has made some dramatic changes to Logic, their flagship audio editing and music production application. In addition to a comprehensive suite of professional tools that provides musicians with everything they need to create in the studio, on the stage, and for the screen, Logic Pro 8, features an intuitive new streamlined interface that makes it easier to write, record, edit, and mix music--all with the sound quality and rock-solid timing you have come to expect from Logic. Join Patrick Copeland, veteran audio engineer, as he gives you a comprehensive look at each aspect of this powerful software program. The HA! QuickSTART Overview gives you the needed edge to be up and running quickly. With its acclaimed power and flexibility for writing, recording, and producing music, it is easy to see why many audio professionals make Logic their weapon of choice in the studio"--Resource description page.
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Description from resource description page (viewed Aug. 13, 2010).
Keywords: Logic (Computer file); Digital audio editors; Music -- Data processing; Sound -- Recording and reproducing -- Digital techniques; Electronic books